Commitment and Change Georges Sorel and the idea of revolution - Vernon, Richard (University of Toronto Press, 2019)
This analysis of Georges Sorel's ideas on revolution and the original translations of some of his little-known writings on this theme offer a critical reassessment of Sorel's place in modern political thought. By turns conservative pessimist, social democrat, revolutionary syndicalist, and reactionary, Sorel is a perplexing figure. He has long been regarded as one of a generation of intellectuals who abandoned reason for violence, theoretical reflection for practical commitment. But according to Sorel -- as the title of his most notorious book makes clear -- the task of the theoretician is to reflect on violence. He maintained that reflection discloses the limited and deficient character of practical thought, but he also recognized that the springs of action escape the grasp of the reflective theorist. It was this distinctness of theory and practice that Soreal attempted to come to terms with in his thinking on revolution. If revolution is a violent action, it is also a process of structural change which the actors themselves do not comprehend. This theme enables the reader to grasp a significant degree of continuity among some of Sorel's bewilderingly diverse positions. Moreover, it accounts for much of his critique of Marxism and his sceptical reflects on Marxian notions of history, class, consciousness, and party. Placed in the context of modern revolutionary thinking, Sorel is an eccentric figure but not an irrelevant one, for his approach points to some of the difficulties in the idea of revolution that were largely overlooked by the 'New Left.'
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019)
Keywords: Sorel, Georges -- 1847-1922; SOCIAL SCIENCE / Sociology / General; Revolution